Evaluating techniques of artificial intelligence for social robots - Barfield, Jessica K. (Information Research an international electronic journal, 2025)
Introduction. Based on techniques of artificial intelligence (AI) robots equipped with algorithms are becoming more social and intelligent as they enter society. As a relatively unexplored topic of research the current study evaluated whether the perception of robot intelligence was influenced by different techniques of AI. Method. In an online study participants viewed two versions of a humanoid robot which varied by their surface colour and stated AI abilities. For each image participants rated the perceived intelligence of the robot. Results. Using an online survey, the results found no statistically significant effect for robot surface colour on judgments of robot intelligence but that robot voice enablement and the ability to detect a user’s face and emotions added significantly to the perception of robot intelligence. In addition, amongst the AI techniques evaluated, text used for human-robot communication was the least effective method for conveying the perception of intelligence for a humanoid robot. Conclusion. As tentative conclusions, the perception of robot intelligence can be based on the specific AI technique used to design the robot, and it appears that the more the human-like AI ability of the robot, the more likely that users will view the robot as intelligent.